The role of mitochondrial function in the pathogenesis of diabetes - Qin, Bo; Wang, Yiying; Ding, Jinlong (Frontiers in Endocrinology, 2025)
Diabetes mellitus is a chronic metabolic disease characterized by abnormally elevated blood sugar levels due to insulin deficiency or insulin resistance, ultimately leading to various serious complications. In this review, we highlighted the significance of mitochondrial functionality in diabetes, concentrating on elements such as mitochondrial energy metabolism, oxidative stress, and their interplay with insulin sensitivity. Mitochondria are essential organelles that are crucial for energy production and integral to cellular metabolic processes. Recent investigations have underscored the role of mitochondrial dysfunction in the advancement of diabetes, uncovering fundamental mechanisms that lead to insulin resistance and elevated blood glucose levels. Present study amalgamates insights from contemporary studies, emphasizing the criticality of mitochondrial integrity in the occurrence of diabetes and its promise as a target for therapeutic intervention. By clarifying these associations, we aspire to offer novel perspectives and pathways for the prevention and management of diabetes.